Women’s empowerment in agriculture and dietary quality across the life course: Evidence from Bangladesh - Sraboni, Esha; Quisumbing, Agnes R. (Elsevier, 2018)
Using nationally-representative survey data from rural Bangladesh, we examine the relationship between women’s empowerment in agriculture and indicators of individual dietary quality. Our findings suggest that women’s empowerment is associated with better dietary quality of individuals within the household, but the strength of this association varies across the life course. Women’s empowerment is correlated with more diverse diets of children under five, but empowerment measures are not consistently associated with increases in nutrient intake for this age group. Rather, maternal schooling and household socio-economic status play a more important role for younger children. Women’s empowerment is positively and significantly associated with adult men’s and women’s dietary diversity and nutrient intakes. Empowerment does not benefit all individuals within the household equally, with gender bias emerging in adolescence. Variations in the strength of the association between women’s empowerment and different individuals’ dietary quality across the life course has implications for the design and targeting of interventions to improve dietary quality, particularly of women, children, and adolescent girls.